Behavioral Determinants of Pregnant Mothers and Husbands in Containing Pregnancy Examination During the Covid-19 Pandemic - Novia Ririn Rustanti; RR. Catur Leny Wulandari (Eduvest - Journal of Universal Studies, 2021)
ANC is a health service provided to pregnant women in an effort to improve the welfare of the mother and fetus. The pandemic (COVID-19) is now a problem faced by 200 countries around the world. The method used in this paper uses a comprehensive strategy, such as searching for articles in research journal databases, searching through the internet, reviewing articles. There are 5 national articles and 5 international articles, analyzed through analysis of objectives, suitability of topics, research methods used, sample size, research ethics, results of each article, and limitations that occur. The results of this study indicate that the increase in anxiety of pregnant women in the era of the COVID-19 pandemic is due to the lack of knowledge of pregnant women about COVID-19 and how to prevent it. In reducing the mother's anxiety level to carry out Antenatal Care checks, a deep understanding of COVID-19 and how to prevent it, and avoiding false news (hoaxes) can be given. The conclusion based on the analysis that has been carried out is, there are factors of maternal anxiety and husband's support in conducting Antenatal Care examinations, namely inaccurate information circulating to the wider community, then the level of knowledge related to covid-19 and its prevention.